TEAMS GAMES TOURNAMENT (TGT) SEBAGAI METODE UNTUK MENINGKATKAN KEAKTIFAN DAN KEMAMPUAN BELAJAR - Widhiastuti, Ratieh; Fachrurrozie, Fachrurrozie (Dinamika Pendidikan, 2014)
The background of this study is the experience in teached Intermediate Accounting 2 last year that showed unsatisfied results. The purpose of this study are to test and to get the empirical evidance on the effectivity of Teams Games Tournament (TGT) as a teaching methode used in Intermediate Accounting 2 to improve Student Partisipations and Learning Competence.60 students of Accounting Education Departement in 4th semester become objects in this study. This study used primary datas collected from tests, observations dan documentations. This research was done in 3 cycles. Each cycles consisted of 5 stages, they were pre-reflecting, planning, acting, observing and post-reflecting. The results showed empirical evidance that Teams Games Tournament (TGT) methode used in Intermediate Accounting 2 can improve Student Partisipations and Learning Competence.